2021
DOI: 10.1088/1742-6596/2119/1/012024
|View full text |Cite
|
Sign up to set email alerts
|

Non-stationary convective heat transfer in an air synthetic impinging jet. Experiment and numerical simulation

Abstract: An unsteady local heat transfer in an air synthetic non-steady-state jet impingement onto a flat plate with a variation of the Reynolds number, nozzle-to-plate distance and pulses frequency is experimentally and numerically studied. Measurements of the averaged and pulsating heat transfer at the stagnation point are conducted using a heat flux sensor. The axisymmetric URANS method and the Reynolds stress model are used for numerical simulations. For local values of heat transfer, zones with the maximum instant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…Lemanov et al, [48] has found that the stagnation Nu rises at short H/d. The intensity of heat transfer is found to diminish as the distance is increased farther and as Re rises.…”
Section: Working Principlesmentioning
confidence: 95%
See 1 more Smart Citation
“…Lemanov et al, [48] has found that the stagnation Nu rises at short H/d. The intensity of heat transfer is found to diminish as the distance is increased farther and as Re rises.…”
Section: Working Principlesmentioning
confidence: 95%
“…In order to simulate the moving diaphragm of the jet as a moving wall boundary, user-defined function (UDF) has been used [29,40,45,52,55]. The governing equations of continuity, momentum and energy based on URANS (Unsteady Reynolds Averaged Navier-Stokes) has been mostly used [26,46,48,49,52,55].…”
Section: Numerical Approachmentioning
confidence: 99%